Effect of An Acidic Organic Industrial Effluent on Dissolution of Calcite, Gernimation and Dry Matter Yield of Sorghum (SORGHUM Bicolor (L) Moench.) - Jhorar, B S; Malik, R S (Annals of Arid Zone, 2016)
An acidic molasses based Hisar distiilery raw effluent ELD was a test effluent. A 85 days pot experiment was carried out in screen house to quantify the eff(ct of irrigating a calcareous (Typic Ustochrept) soil with ELD at its various water dilution on calcite dissolution, carbonate and bicarbonate anionic balance, germination and dry mailer yield of sorghum cv HC 260. The water dilution treatments of ELD were such as to contain biological oxygen demand (BOD) equal to 250. 500, 750, 1000, 1250.2000,4000,8000, 16000 and 32COO mg L-1. Dissolution percentage of soil calcite increased with decreasing ELD water dilutions. During irrigation soil carbonate concentration remained almost static while that of bicarbonate increased with decreasing water dilutions of ELD. Irrigation with diluted eflluent increased germination and dry matter yield to reach maxima at 500 and 750 mg L-1 eflluent. Critical BOD for these parameters was 1100 mg L-1. This study has shown that application of diluted acidic organic industrial effluent may provide a feasible and suitable technology for managing calcareous soils.